FOXA1 is a potential oncogene in anaplastic thyroid carcinoma - TONER, MARY ELIZABETH; SHEILS, ORLA (My University, 2009)
Purpose: FOXA1 is a mammalian endodermal transcription factor belonging to the human forkhead box gene family that plays a role in certain tumor types. Here, we investigated the potential role of FOXA1 in human thyroid carcinomas. Experimental Design: We examined the level of FOXA1 expression and gene copy number by immunohistochemistry and fluorescence in situ hybridization, respectively, in a cohort of benign and malignant thyroid tumors. In addition, we examined the role of FOXA1 in the proliferation of an undifferentiated thyroid carcinoma cell line by short hairpin RNA-mediated silencing. Results: We show that FOXA1 is overexpressed in human anaplastic thyroid carcinomas (ATC). In addition, we identify FOXA1 DNA copy number gain within the 14q21.1 locus in both an ATC cell line and human ATC cases. Silencing of FOXA1 in an ATC cell line causes G1 growth arrest and reduction of cell proliferation. Moreover, we observe a potential link between FOXA1 and the cell cycle machinery by identifying p27kip1 up-regulation on FOXA1 silencing. Conclusions:FOXA1 is overexpressed in aggressive thyroid cancers and involved in cell cycle progression in an ATC cell line. Therefore, FOXA1 may be an important oncogene in thyroid tumorigenesis and a potential new therapeutic target for the treatment of anaplastic thyroid cancers.
PUBLISHED
PMID: 19470727
Keywords: Oncology; FOXA1